EFEKTIVITAS PEMBERIAN BEBERAPA JENIS DAN DOSIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH(Allium ascalonicum L.) - Abudzar Muharam Miraza; Meiriani Meiriani; Ferry Ezra Sitepu (Jurnal Agroekoteknologi, 2014)
Effectiveness of the administration of multiple types and doses of organic liquid fertilizer on thegrowth and yield of Shallot (Allium ascalonicum L.). The research had been conducted at Jl.Khairuna Fauzi no. 11, Komplek Kejaksaan, Medan selayangat+ 25 m asl from April until June2012. The research using factorial randomized block design with the same treatment dosage factor:100 ml, 200 ml dan 300 ml/L water. Liquid Organic Fertilizer (P) was divided be three levels P:Liquid organic fertilizer of cow’s blood. Q: Liquid organic fertilizer of cow manure. R: Liquidorganic fertilizer of tea extract. The parameters were observed : plant height per clump, number ofleaves per clump, number of tillers per hill, number of cloves per hill, tuber diameter per sample,tuber fresh weight per hill, tuber dry weight per hill, fresh tuber production per plot, dried tuberproduction per plot.The results showed that the liquid fertilizer had given were significant on allparameters of growth and production.Key words : Liquid organic fertilizer, dosage, shallot.